ETUDE ET DIMENSIONNEMENT D'UN SYSTEME DE POMPAGE PHOTOVOLTAÏQUE DANS UNE EXPLOITATION AGRICOLE À LAGHOUAT - GUEDDOUDA Med Taha Adnane; Vilbois leila (UNIVERSITE Amar Telidji de Laghouat.FACULTE DE TECHNOLOGIE.DEPARTEMENT D’ELECTROTECHNIQUE, 2022)
The work presented in this research is a study of a drip irrigation system with a solar pumping system. The study area is located near "Bouchakeur" which is located in Laghouat in southern Algeria. We first presented the photovoltaic system and the pumps, then we defined the parameters necessary for our study which are: - the climate, the water sources and the sunshine. The strong sunshine of the region allowed us to choose the appropriate solar water pumping using solar energy transmitted by the solar generator composed of photovoltaic panels and an inverter. Intermittent sunshine being a little annoying so for this we found it useful to use water storage in a reservoir, the amount of water stored remains decent for irrigation, overall the project is economically laudable in the long term.
OPTION : Energies Renouvelables